2017
DOI: 10.1128/jvi.02275-16
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic and Amino Acid Sequences Support Structure-Based Viral Classification

Abstract: Viral capsids ensure viral genome integrity by protecting the enclosed nucleic acids. Interactions between the genome and capsid and between individual capsid proteins (i.e., capsid architecture) are intimate and are expected to be characterized by strong evolutionary conservation. For this reason, a capsid structure-based viral classification has been proposed as a way to bring order to the viral universe. The seeming lack of sufficient sequence similarity to reproduce this classification has made it difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…Phylogenetic analyses were performed separately on the MCP and the pATPase using the resulting datasets within the maximum likelihood (ML) framework. DJR eukaryoviruses were clearly separated from archaeoviruses and bacterioviruses in both trees, in agreement with previous observations made using pairwise sequence similarities or comparative structural analyses ( 11 , 24 ). In particular, unlike the result obtained with the sequence similarity network, members of the Lavidaviridae were grouped with other eukaryoviruses in the pATPase tree.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Phylogenetic analyses were performed separately on the MCP and the pATPase using the resulting datasets within the maximum likelihood (ML) framework. DJR eukaryoviruses were clearly separated from archaeoviruses and bacterioviruses in both trees, in agreement with previous observations made using pairwise sequence similarities or comparative structural analyses ( 11 , 24 ). In particular, unlike the result obtained with the sequence similarity network, members of the Lavidaviridae were grouped with other eukaryoviruses in the pATPase tree.…”
Section: Resultssupporting
confidence: 91%
“…In a phylogenetic tree based on the common core of the MCP published in 2013, the viruses of the DJR PRD1-adenovirus were divided into three groups: one corresponding to Adenoviruses, another grouping NCLDVs (represented by two members) with Lavidaviridae , and the third one including viruses infecting Archaea and Bacteria ( 11 ). Furthermore, the evolutionary relationships among the PRD1-adenovirus lineage were recently investigated using pairwise sequence similarities between DJR viruses ( 20 , 24 ). These analyses demonstrated that there are evolutionary links between archaeoviruses and bacterioviruses as well as eukaryoviruses and bacterioviruses.…”
Section: Introductionmentioning
confidence: 99%
“…No protein even remotely similar to the usually abundant major capsid protein (MCP), a predicted DNA-binding core protein, or a DNA-packaging ATPase, hallmarks of most eukaryotic large DNA viruses, was detected. In particular, a P. salinus hypothetical protein (previously ps_862 now reannotated psal_cds_450) recently suggested by Sinclair et al 16 to be a strong major capsid protein candidate was not detected in the P. salinus virions, nor its homologs in the other strain proteomes. This result emphasizes the need for the experimental validation of computer predictions made from the "twilight zone" of sequence similarity.…”
Section: Comparative Proteomic Of Pandoravirus Particles (Pandoravirimentioning
confidence: 85%
“…Besides the MCPs, these viruses employ similar virion assembly and maturation as well as genome packaging mechanisms, which are not found in viruses outside this virus assemblage (46). The second architectural class encompasses highly diverse dsDNA viruses with the vertical double-jelly-roll (DJR) MCPs, including members of the bacterial virus families Corticoviridae and Tectiviridae, archaeal viruses of the family Turriviridae, and eukaryotic viruses of the families Adenoviridae and Lavidaviridae as well as the proposed order "Megavirales" that comprises most of the large and giant eukaryotic viruses (47)(48)(49). Most viruses within this class contain an internal membrane vesicle located between the protein capsid and the dsDNA genome and carry genes that encode homologous A32-like genome packaging ATPases not found in other virus groups.…”
Section: Discussionmentioning
confidence: 99%